2019
DOI: 10.1002/lary.28294
|View full text |Cite
|
Sign up to set email alerts
|

Total endoscopic stapes surgery: Systematic review and pooled analysis of audiological outcomes

Abstract: Objective: This study evaluates the current evidence base for total endoscopic stapes surgery, specifically to establish current efficacy and safety of the technique within clinical practice.Data Sources: A systematic review of the literature on endoscopic stapes surgery was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis checklist. A comprehensive search of PubMed, Embase, and the Cochrane Central Register of Controlled Trials database for relevant publications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…21 Hall et al reported in a pooled analysis on 14 endoscopic studies that the rate of ABG closure to <20 db HL was found to be 95.3%, whereas closure to <10 db HL was 76.6%, which aligns closely with our results. 22 Statistically significant changes of the postoperative BC threshold were not reported: only 1% of cases in our series showed postoperative SNHL, which is close to data reported in publications both on microscopic and endoscopic SS so far. [22][23][24] Similarly, a review of over 3,000 cases reported a rate of 0.5% of postoperative SNHL in microscopic stapedotomy.…”
Section: Functional Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…21 Hall et al reported in a pooled analysis on 14 endoscopic studies that the rate of ABG closure to <20 db HL was found to be 95.3%, whereas closure to <10 db HL was 76.6%, which aligns closely with our results. 22 Statistically significant changes of the postoperative BC threshold were not reported: only 1% of cases in our series showed postoperative SNHL, which is close to data reported in publications both on microscopic and endoscopic SS so far. [22][23][24] Similarly, a review of over 3,000 cases reported a rate of 0.5% of postoperative SNHL in microscopic stapedotomy.…”
Section: Functional Resultssupporting
confidence: 89%
“…22 Statistically significant changes of the postoperative BC threshold were not reported: only 1% of cases in our series showed postoperative SNHL, which is close to data reported in publications both on microscopic and endoscopic SS so far. [22][23][24] Similarly, a review of over 3,000 cases reported a rate of 0.5% of postoperative SNHL in microscopic stapedotomy. 25 Direct trauma due to onehanded surgical maneuvers and heating caused by the light of the endoscope have been frequently questioned as possible risks for inner ear damage during EES 26 ; however, our results did not support this hypothesis, as the use of the endoscope has proven to be a safe tool in our large cohort, as previously described.…”
Section: Functional Resultssupporting
confidence: 89%
“…At first, PLFs were observed in post-stapedectomy patients where perilymph would leak around a prosthesis placed into the oval window due to a failure of the seal around or under the prosthesis ( 7 – 9 ). Though techniques for stapes surgery have advanced, PLFs still occur as a complication in ~1% of stapedotomy procedures ( 10 ) and may be present in up to one-third of individuals requiring revision stapedectomies ( 11 ).…”
Section: Etiologymentioning
confidence: 99%
“…and Koukkoullis et al . 2830 Exceptionally, Fang et al . observed a statistically significant difference in favour of the endoscopic technique, demonstrating its superiority.…”
Section: Discussionmentioning
confidence: 99%